Kissing girls on Shabbat : a memoir - Glass, Sara Dr (One Signal Publishers/Atria, 2024)
Growing up in the Hasidic community of Brooklyn's Borough Park, Sara Glass knew one painful truth: what was expected of her and what she desperately wanted were impossibly opposed. Tormented by her attraction to women and trapped in a loveless arranged marriage, she found herself unable to conform to her religious upbringing and soon, she made the difficult decision to walk away from the world she knew. Sara's journey to self-acceptance began with the challenging battle for a divorce and custody of her children, an act that left her on the verge of estrangement from her family and community. Controlled by the fear of losing custody of her two children, she forced herself to remain loyal to the compulsory heteronormativity baked into Hasidic Judaism and married again. But after suffering profound loss and a shocking sexual assault, Sara decided to finally be completely true to herself. Kissing Girls on Shabbat is not only a love letter to Glass's children, herself, and her family--it is an unflinching window into the world of ultra-conservative Orthodox Jewish communities and an inspiring celebration of learning to love yourself.